Dynamics of ?-Singular Vortexes on a Rotating Sphere and Stability of Paired Action Centers of the Atmosphere - Mokhov, I. I.; Chefranov, S. G.; Chefranov, A. G. (Maik Nauka/Interperiodica/Springer, 2010)
[Abstract Not Available]
Keywords: Point Vortices